Inhibitory role of inducible cAMP early repressor (ICER) in methamphetamine-induced locomotor sensitization. - Wenhua Han; Yukio Takamatsu; Hideko Yamamoto; Shinya Kasai; Shogo Endo; Tomoaki Shirao; Nobuhiko Kojima; Kazutaka Ikeda (PLoS ONE, 2011)
BACKGROUND: The inducible cyclic adenosine monophosphate (cAMP) early repressor (ICER) is highly expressed in the central nervous system and functions as a repressor of cAMP response element-binding protein (CREB) transcription. The present study sought to clarify the role of ICER in the effects of methamphetamine (METH). METHODS AND FINDINGS: We tested METH-induced locomotor sensitization in wildtype mice, ICER knockout mice, and ICER I-overexpressing mice. Both ICER wildtype mice and knockout mice displayed increased locomotor activity after continuous injections of METH. However, ICER knockout mice displayed a tendency toward higher locomotor activity compared with wildtype mice, although no significant difference was observed between the two genotypes. Moreover, compared with wildtype mice, ICER I-overexpressing mice displayed a significant decrease in METH-induced locomotor sensitization. Furthermore, Western blot analysis and quantitative real-time reverse transcription polymerase chain reaction demonstrated that ICER overexpression abolished the METH-induced increase in CREB expression and repressed cocaine- and amphetamine-regulated transcript (CART) and prodynorphin (Pdyn) expression in mice. The decreased CART and Pdyn mRNA expression levels in vivo may underlie the inhibitory role of ICER in METH-induced locomotor sensitization. CONCLUSIONS: Our data suggest that ICER plays an inhibitory role in METH-induced locomotor sensitization.